2006
DOI: 10.1038/sj.ejcn.1602374
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on vitamin D status and bone turnover markers in young adults

Abstract: Objective: To assess the vitamin D status of healthy young people living in Northern Ireland and the effect of vitamin D supplementation on vitamin D status and bone turnover. Design: Double-blinded randomised controlled intervention study. Setting: University of Ulster, Coleraine, Northern Ireland. Subjects: In total, 30 apparently healthy students (15 male and 15 female subjects), aged 18-27 years, were recruited from the university, with 27 completing the intervention. Interventions: Subjects were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
36
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 56 publications
7
36
1
Order By: Relevance
“…Secretion of PTH is regulated primarily by a drop in serum calcium [31,32] and does not appear to be affected by vitamin D deficiency until serum 25(OH)D concentrations drop below 30-40 nmol/L [16,32,33]. This may explain the lack of PTH response to supplementation in this study.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Secretion of PTH is regulated primarily by a drop in serum calcium [31,32] and does not appear to be affected by vitamin D deficiency until serum 25(OH)D concentrations drop below 30-40 nmol/L [16,32,33]. This may explain the lack of PTH response to supplementation in this study.…”
Section: Discussionmentioning
confidence: 66%
“…Hitz et al [15] observed an increase in bone mineral density (BMD), concurrent with decreased PTH and bone turnover in older people under 70 years and reduced loss in those over 70 years. However there was no change in healthy students aged 18-27 years [16].…”
Section: Introductionmentioning
confidence: 58%
“…At baseline, 25(OH)D concentration (mean ± SD) did not statistically differ between the calcium plus vitamin D group (48±16 nmol/L) and the calcium group (56±19 nmol/L). Analysis of covariance (ANCOVA) showed that post-supplementation 25(OH)D concentrations significantly differed between the treatment groups, namely 87±25 nmol/L in the calcium plus vitamin D group and 48±17 nmol/L in the calcium group (ANCOVA P<0.0001) (Barnes et al 2006). …”
Section: Adultsmentioning
confidence: 99%
“…Dawodu and colleagues also implicate cultural dress codes, which encourage extensive body covering. Moreover, the high levels of obesity of residents in the UAE countries, the relatively darker skin pigmentation, and the presence of dust in the atmosphere may also contribute by reducing the skin's ability to synthesize VTD (Barnes et al, 2006).…”
mentioning
confidence: 99%